Penggunaan Tes Online “Testmoz” Terintegrasi dengan Googleclassroom sebagai Alternatif Alat Pembelajaran Daring - Ivan Ashif Ardhana (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[The Use of the Online "Testmoz" Test Integrated with Google Classroom as an Alternative Online Learning Tool]. This study aimed to explore students’ acceptance level of the online-based assessment tool “Testmoz” integrated with Google classroom on chemistry courses. The subjects were 51 students of the fifth semester at Jurusan Tadris Kimia IAIN Tulungagung selected by purposive sampling. The method used in this study was a one-shot case study design. Data obtained from students’ questionnaires and interviews before the Covid-19 pandemic start to begin. The result shows 93,30% accepting the level of Testmoz integrated with Google classroom. These findings were supported by students’ interview data as a user that overall result was positive and shows support. The additional result shows the high interest of rural students through learning innovation using the help of information technology. These results may support the learning process on pandemic conditions that use digital platforms such as the Learning Management System (LMS) as supporting tools of learning in this era.